The journal of Wong Ming-Chung : a Chinese miner - Yep, Laurence (New York : Scholastic, 2000)
A young Chinese boy nicknamed Runt records his experiences in a journal as he travels from southern China to California in 1852 to join his uncle during the Gold Rush.
Keywords: California -- Fiction -- Gold discoveries; Gold mines and mining -- Fiction; Chinese Americans -- Fiction; Uncles -- Fiction; Diaries -- Fiction